Aberrant somatosensory phase synchronization in children with hemiplegic cerebral palsy. (25th September 2021) - Song, Yanlong; Renoul, Emmanuelle; Acord, Stephanie; Johnson, Yvette R.; Marks, Warren; Alexandrakis, George; Papadelis, Christos
Highlights: Phase synchrony estimated from MEG-recorded somatosensory evoked fields. Children with hemiplegic cerebral palsy showed aberrant phase synchronization. More- and less-affected hemispheres with differential synchrony characteristics. Abnormal somatosensory functional connectivity with hemiplegic cerebral palsy. Abstract: Children with hemiplegic cerebral palsy (HCP) often show disturbances of somatosensation. Despite extensive evidence of somatosensory deficits, neurophysiological alterations associated with somatosensory deficits in children with HCP have not been elucidated. Here, we aim to assess phase synchrony within and between contralateral primary (S1) and secondary (S2) somatosensory areas in children with HCP. Intra-regional and inter-regional phase synchronizations within and between S1 and S2 were estimated from somatosensory evoked fields (SEFs) in response to passive pneumatic stimulation of contralateral upper extremities and recorded with pediatric magnetoencephalography (MEG) in children with HCP and typically developing (TD) children. We found aberrant phase synchronizations within S1 and between S1 and S2 in both hemispheres in children with HCP. Specifically, the less-affected (LA) hemisphere demonstrated diminished phase synchronizations after the stimulus onset up to 120 ms compared to the more-affected (MA) hemisphere and the dominant hemisphere of TD children, while the MA hemisphere showed enhanced phase synchronizations after 100 ms compared to the LA hemisphere and the TD dominant hemisphere. Our findings indicate abnormal somatosensory functional connectivity in both hemispheres of children with HCP.